A Progressive Early Mobilization Program Is Significantly Associated With Clinical and Economic Improvement: A Single-Center Quality Comparison Study. Issue 9 (September 2019) - Liu, Keibun; Ogura, Takayuki; Takahashi, Kunihiko; Nakamura, Mitsunobu; Ohtake, Hiroaki; Fujiduka, Kenji; Abe, Emi; Oosaki, Hitoshi; Miyazaki, Dai; Suzuki, Hiroyuki; Nishikimi, Mitsuaki; Komatsu, Mamoru; et al.
Abstract : Objectives: To determine whether a progressive early mobilization protocol improves patient outcomes, including in-hospital mortality and total hospital costs. Design: Retrospective preintervention and postintervention quality comparison study. Settings: Single tertiary community hospital with a 12-bed closed-mixed ICU. Patients: All consecutive patients 18 years old or older were eligible. Patients who met exclusion criteria or were discharged from the ICU within 48 hours were excluded. Patients from January 2014 to May 2015 were defined as the preintervention group (group A) and from June 2015 to December 2016 was the postintervention group (group B). Intervention: Maebashi early mobilization protocol. Measurements and Main Results: Group A included 204 patients and group B included 187 patients. Baseline characteristics evaluated include age, severity, mechanical ventilation, and extracorporeal membrane oxygenation, and in group B additional comorbidities and use of steroids. Hospital mortality was reduced in group B (adjusted hazard ratio, 0.25; 95% CI, 0.13–0.49; p < 0.01). This early mobilization protocol is significantly associated with decreased mortality, even after adjusting for baseline characteristics such as sedation. Total hospital costs decreased from 29, 220 to 22, 706. The decrease occurred soon after initiating the intervention and this effect was sustained. The estimated effect was –5, 167 per patient, a 27% reduction. Reductions in ICU and hospital lengths of stay, time on mechanical ventilation, and improvement in physical function at hospital discharge were also seen. The change in Sequential Organ Failure Assessment score and Sequential Organ Failure Assessment score at ICU discharge were significantly reduced after the intervention, despite a similar Sequential Organ Failure Assessment score at admission and at maximum. Conclusions: In-hospital mortality and total hospital costs are reduced after the introduction of a progressive early mobilization program, which is significantly associated with decreased mortality. Cost savings were realized early after the intervention and sustained. Further prospective studies to investigate causality are warranted. Abstract : Supplemental Digital Content is available in the text.